KAJIAN NORMATIF: KEDUDUKAN DAN PERAN PENDIDIKAN AGAMA ISLAM DAN SISTEM PENDIDIKAN NASIONAL INDONESIA - Reni Febriani; Nur Annisa; Cita Suci; Muhammad Syaifuddin (STKIP Subang, 2026)
Islamic Religious Education is essentially a planned and systematic effort to guide, teach, and develop the potential of students based on the values ​​of Islamic teachings, with the aim of forming human beings who are insan kamil—faithful, knowledgeable, and have noble character. The purpose of this research was to normatively examine the position and role of Islamic Religious Education in the Indonesian National education system. This research method uses a descriptive qualitative approach through library research that explores various scientific and relevant sources. The results of the study found that the position of Islamic Religious Education in the national education system is very strong as a compulsory subject and is a major component in achieving national education goals. The role of Islamic Religious Education in the national education system is very fundamental, including the formation of character and noble character, the development of the spiritual dimension of students, the building of tolerance and national unity, and the improvement of the quality of national education as a whole.